2016
DOI: 10.1002/mrd.22692
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and mRNA expression of developmentally important genes in bovine oocytes collected from donors of different age categories

Abstract: Epigenetic changes are critical for the acquisition of developmental potential by oocytes and embryos, yet these changes may be sensitive to maternal ageing. Here, we investigated the impact of maternal ageing on DNA methylation and mRNA expression in a panel of eight genes that are critically involved in oocyte and embryo development. Bovine oocytes were collected from donors of three different age categories-prepubertal (9-12 months old), mature (3-7 years old), and aged (8-11 years old)-and were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This accords with a recent study of the Snrpn and Kcnq1ot1 gDMRs in mouse oocytes that reported normal methylation acquisition irrespective of age, as well as no effect on maintenance of methylation to the blastocyst stage following fertilisation of oocytes from aged females (Kindsfather et al, 2019). Methylation in embryos and placentas at embryonic day 10.5 of aged mice was previously found to be normal at both maternal and paternal gDMRs (Snrpn, U2af1-rs1, Peg1, Igf2r, H19) (Lopes et al 2009); methylation of the SNPRN gDMR is also reported to be unaffected by age in bovine oocytes (Mattern et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…This accords with a recent study of the Snrpn and Kcnq1ot1 gDMRs in mouse oocytes that reported normal methylation acquisition irrespective of age, as well as no effect on maintenance of methylation to the blastocyst stage following fertilisation of oocytes from aged females (Kindsfather et al, 2019). Methylation in embryos and placentas at embryonic day 10.5 of aged mice was previously found to be normal at both maternal and paternal gDMRs (Snrpn, U2af1-rs1, Peg1, Igf2r, H19) (Lopes et al 2009); methylation of the SNPRN gDMR is also reported to be unaffected by age in bovine oocytes (Mattern et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In the present work, a model for the study of age-associated infertility in cattle oocytes was developed. Due to the similarities to human pregnancy, follicular and endocrine events [48,49], this model may also be useful for human research, avoiding the ethical and physical restrictions that hamper these studies in human oocytes. Our model for aging female gametes proved to be very efficient and suitable for studying different problems associated with reproductive aging and fertility impairment, currently one of most critical challenges in the world.…”
Section: Discussionmentioning
confidence: 99%
“…These studies primarily revealed the methylation of highly condensed repetitive DNA or the methylation level of sequences represented on the array. Although numerous studies have been performed to evaluate the methylation level of selected genes and regulatory regions during bovine embryo development [21,[24][25][26], the complete characterization of DNA methylation at the single-base level has not been reported. This characterization is critical to understanding the epigenetic reprogramming and regulation that occurs during normal, bovine embryonic development in vivo, and to providing insight into the epigenetic alterations that occur during in vitro maturation of oocytes and culture of embryos after in vitro fertilization.…”
Section: Introductionmentioning
confidence: 99%